Development of Flipped Classroom Based Learning Devices Assisted by the Nearpod Application in Integrated Thematic Learning in Third Class of Elementary Schools - Santia Indah Purnama; Yeni Erita; Ahmad Fauzan; Darmansyah; Darnelis (Jurnal Penelitian Pendidikan IPA, 2024)
The educational era influenced by the industrial revolution 4.0 is called Education 4.0, which is characterized by the use of computerized innovation in every educational cycle. The problem that researchers encountered at SDN 8 Lawang Kidul and SDN 16 Lawang Kidul was the lack of use of varied learning media and the use of technology. This research aims to develop a Nearpod application-assisted learning tool based on Flipped Classroom for integrated thematic learning in class III elementary schools that is valid, practical and effective. This research is included in Research and Development research which uses the ADDIE development model. Data collection uses observation, questionnaire interviews and written tests. The research subjects were class III students at SDN 8 Lawang Kidul and SDN 16 Lawang Kidul. Data analysis uses a Likert scale by looking at validation analysis, practicality and effectiveness of the Nearpod Application-Assisted Learning Tool based on Flipped Classroom. This research produced a flipped classroom-based learning tool assisted by the nearpod application in integrated thematic learning in class III of this elementary school, namely for material expert validators who got a score of 92%, media expert validators got a score of 96% and language expert validators got a score of 92%. For the practicality questionnaire, teacher responses scored 95.5% and for the practicality questionnaire, student responses scored 90.04%, which is categorized as very practical. The effectiveness test shows an increase in learning outcomes from an average of 54.002 to 87.46. Based on these results, it can be concluded that the flipped classroom-based learning device assisted by the nearpod application in integrated thematic learning in class III elementary schools meets the valid, practical and effective categories so that it can improve student learning outcomes.